Large-scale capacitive touch panels : sensor pattern design, sampling and interpolation - Akhtar, Humza (2017)
A touch panel is an input device for human computer interaction. It consists of a network of sensors, a sampling circuit and a controller for detecting and locating a touch input. Touch input can come from either finger or stylus depending upon the type of touch technology. These touch panels provide an intuitive and collaborative workspace so that people can perform various tasks without the use of traditional input devices like keyboard and mouse, and with the use of their fingers. Our research studies and tries to improve upon the traditional design and algorithms for capacitive touch technology.